THE PAST AND THE PROSPECT OF ADMINISTRATIVE DIVISION OF GEORGIA - Jikia, Mariam (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2019)
Georgia has rarely been able to independently determine the form of administrative division of the country. Taking into consideration foreign and domestic policies, economic conditions and other factors, it was becoming necessary to divide the country into certain territorial units, however Georgia has never been a strictly centralized state. Presented paper discusses the issue of administrative division in legal documents created in independent Georgia. The issue is debated according to the first constitution of democratic republic of Georgia and the second constitution adopted in 1995. Paper also reviews all the amendments of Georgian Constitution during last 20 years, that do not consider any significant changes of discussed issue. Author analyses what is the best administrative division for Georgia considering existing 2 conflicts and underlines positive and negative aspects of Federalism and Unitarism.